RELEVANSI QIYAS DALAM STRUKTUR HUKUM ISLAM - Ahmad Fauzi (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2022)
Al-Qur'an, Hadith, Ijma, and Qiyas are the four main texts of Islamic law accepted by the scholars. On the other hand, Islamic law that is often cited by religious figures other than those listed above is istihsan, maslahah mursalah, istishab,